Analisis Pengaruh Perubahan Kekakuan Pondasi Kapal Ikan Tradisional terhadap Amplitudo Getaran - Lekatompessy, Debby Raynold (TEKNIK)
The ship with the outboard engine is intended to make it easier for fishers to operate and maintain. However, the magnitude of the vibration due to the excitation of the engine during operation adversely affects the surrounding structures. It is evidenced by measuring the vibration amplitude of more than 0.02 mm at several points around the ship engine foundation. This study aims to reduce these vibrations by changing the canal's dimensions as a foundation and using damping rubber as the simplest solution. The analysis was carried out by calculating the vibration parameters of 2 types of machines, SR1110 and S1100. The numerical method is used to calculate the vibration's amplitude by varying the value of channel stiffness and rubber damping on the machine foundation. Supporting data is obtained by measuring the vibration amplitude at several points around the foundation. The magnitude of the previous vibration amplitude is 0.078 mm for the SR1110 type and 0.069 mm for the S1100 type, which exceeds the limit still. The amplitude is reduced by changing the foundation's dimensions and using a rubber damper (c). With the new foundation dimensions, the amplitude for the diesel engine type SR1110 becomes 0.0245 mm and type S1100 becomes 0.0238 mm. Increased stiffness and the addition of rubber succeeded in reducing the vibration amplitude by a significant value. The amplitude was reduced by 69% for the SR1110 engine type and 65% for the S1100 engine type within the allowable limit of less than 0.02 mm to 0.03 mm based on Barkan's observation results.